2020
DOI: 10.48550/arxiv.2012.15297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trapping Sets of Quantum LDPC Codes

Nithin Raveendran,
Bane Vasić

Abstract: Iterative decoders for finite length quantum lowdensity parity-check (QLDPC) codes are attractive because their hardware complexity scales only linearly with the number of physical qubits. However, they are impacted by short cycles, detrimental graphical configurations known as trapping sets (TSs) present in a code graph as well as symmetric degeneracy of errors. These factors significantly degrade the decoder decoding probability performance, and cause so-called error floor. In this paper, we establish a syst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…For nondegenerate quantum codes, their decoding behaviors are like classical codes and BP usually works well with the techniques of message normalization and message scheduling (see examples in [25,26]). However, BP fails to decode highly-degenerate quantum codes [33][34][35], such as the surface codes [8,9]. Next we will analyze the energy topology of a degenerate quantum code.…”
Section: Energy Topologymentioning
confidence: 99%
See 2 more Smart Citations
“…For nondegenerate quantum codes, their decoding behaviors are like classical codes and BP usually works well with the techniques of message normalization and message scheduling (see examples in [25,26]). However, BP fails to decode highly-degenerate quantum codes [33][34][35], such as the surface codes [8,9]. Next we will analyze the energy topology of a degenerate quantum code.…”
Section: Energy Topologymentioning
confidence: 99%
“…Since a target δ m > 0 (a target ∆ m > 0), we may also consider another energy function to focus on negative ∆ m (i.e., to focus on mismatched checks) by where ẑm = Ê, S m . This energy function is used by a simplified BP called bit-flipping BP [30,31,35,78,79], which decides the update direction (which bit to flip) by minimizing the number of unmatched syndrome bits between z and ẑ. Bit-flipping BP has very low complexity and is useful for analyzing the convergence, since it only tracks the hard-decision information of the variable nodes. (Bit-flipping BP can also be used in practice, e.g., it was used in decoding expander codes [78].…”
Section: Appendix C: Energy Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first explain the serial schedule that will be conducted in the following simulations. In [24], it is demonstrated that based on the raw check matrix of the [[129, 28]] HP code, the parallel BP 4 decoding does not perform well due to decoding oscillation (which is caused by the numerous short cycles and symmetric sub-graphs in the Tanner graph [24], [31]); on the other hand, the serial BP 4 along variable nodes performs quite well by using the raw matrix [24]. We have created a check matrix so that each of its column has weight ≥ 2 for Theorem 2; however, the serial update along variable nodes is too aggressive at certain variable node for the new check matrix (when computing the hard-decision and outgoing messages).…”
Section: B Simulation Resultsmentioning
confidence: 99%
“…3). The message update order plays an important role in BP, especially when the Tanner graph has numerous short cycles [24], [31].…”
Section: A the Ds-bp Algorithmmentioning
confidence: 99%